Položaj Katoliške Cerkve na Kamniškem v obdobju 1965-1975 - Hančič, Damjan (Bogoslovni vestnik, 2020)
After the end of the Second World War, the Communist authorities had a distinctly negative attitude towards all religious communities, especially towards the Catholic Church, due to political and ideological reasons. The Party's strong tendencies to control the Church and its members (priests or socially engaged laypeople) and cases of its efforts to limit the Church's social influence can also be found in the area of the Municipality of Kamnik. Based on the material of the organisation of the League of Communists from the Municipality of Kamnik, the article shows the position of the Catholic Church in the area of the municipality from the end of the 1960s to the middle of the 1970s. On the one hand, this was the time when the Catholic Church aimed to expand the space in which it operated on the local level as well due to the implementation of the conclusions from the Second Vatican Council and the normalisation of the diplomatic relations between Yugoslavia and the Holy See; on the other hand, the Party still attempted to limit the Church's influence in the society during this time.
Keywords: 1965-1975; Catholic Church; Kamnik; Katoliška Cerkev; League of Communists; religious communities; Slovenia; Slovenija; verske skupnosti; zveza komunistov